Penguatan Pendidikan Keluarga Melalui Majelis Ta’lim Muslimat Desa Poreh Lenteng - Moh. Rifqi Rahman; Evi Fatimatur Rusydiyah; Rif'atul Fadilah (Yayasan Keluarga Guru Mandiri, 2024)
The rural community of Poreh exhibits potential through its proactive community leaders driving educational initiatives. However, the prevalence of residents with low educational qualifications underscores the need for optimization in educational quality. This service-oriented research aims to optimize the initiatives of mosque administrators and influential figures in Poreh Lenteng Village, focusing on enhancing community education through the Muslim women's study group. Specifically, the research aims to systematize material for strengthening family education to facilitate practical implementation for each study group member. Employing the ABCD (Asset Based Community Development) approach, the research progresses through stages including discovery, dream, design, define, destiny, and reflection. The outcomes highlight the emphasis on developing material to fortify family education, previously rudimentary and lacking direction. This initiative aims to provide cognitive and practical insights to study group members, fostering an educational environment within their family settings. The research suggests diversifying methods for Muslim women's activities beyond traditional lecture-based approaches.